High performance sport and sustainability: a contradiction of terms? - Barker, D.; Barker-Ruchti, N.; Wals, A.; Tinning, R. (Reflective Practice. International and Multidisciplinary Perspectives, 2014)
Success in high performance sport has always been highly valued. Today, lucrative contracts, sponsorship deals and opportunities for celebrity status are balanced against substantial time spent training and high chances of failure. With pressure mounting on athletes to make the most of their athletic `investment`, the temptation to compromise their future well-being by exploiting their bodies for short-term gain and/or by cheating is growing. The aim of this paper is to explore the utility of sustainability science for thinking about these types of issues. Sustainability science is an emerging field which seeks to preserve the well-being of the planet and those on it by exploring the potential of nature and culture without compromising the future resource base. It specializes in developing holistic perspectives, considering multiple time scales, optimizing current systems without compromising the carrying capacity of the Earth, but also questioning the values and principles that dominate current ways of producing and consuming. Sustainability science acknowledges that we live in a rapidly changing world characterized by high levels of complexity and uncertainty. The proposition developed in this paper is that an exploration of sustainability perspectives can be generative in re-thinking and re-orienting the principles of high level competitive sports. contradiction of terms?.